2014
DOI: 10.1113/jphysiol.2014.279968
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of enteric neurons by interleukin‐6 and corticotropin‐releasing factor contributes to visceral hypersensitivity and altered colonic motility in a rat model of irritable bowel syndrome

Abstract: Key pointsr Hyperactivity of the stress system and low-grade immune activation characterize the functional bowel disorder irritable bowel syndrome (IBS).r These studies show that interleukin (IL)-6 and IL-8 and the stress hormone corticotropin-releasing factor (CRF), present in IBS plasma, have functional effects on gastrointestinal activity by stimulating myenteric neurons and colonic contractions.r Moreover, in the Wistar Kyoto rat model of IBS, which exhibits altered gastrointestinal motility and visceral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 54 publications
7
100
4
Order By: Relevance
“…Cytokines facilitate cell-to-cell signaling in an immune response, but may also participate in modulating intrinsic and afferent nerve activity. Indeed, IL-6 (6, 63), IL-1β (86) and tumor necrosis factor α (72) have direct actions on enteric neuronal activation and we observed that the neurostimulatory effects of IBS plasma on rat submucosal and myenteric neurons is dependent on IL-6, IL-8 and CRF (6,62). Such cytokines stimulate sensitization of nociceptors, which would increase the excitability of afferent endings innervating the colon.…”
Section: Concentrations Of Pro-inflammatory Cytokines Such As Interlementioning
confidence: 74%
See 2 more Smart Citations
“…Cytokines facilitate cell-to-cell signaling in an immune response, but may also participate in modulating intrinsic and afferent nerve activity. Indeed, IL-6 (6, 63), IL-1β (86) and tumor necrosis factor α (72) have direct actions on enteric neuronal activation and we observed that the neurostimulatory effects of IBS plasma on rat submucosal and myenteric neurons is dependent on IL-6, IL-8 and CRF (6,62). Such cytokines stimulate sensitization of nociceptors, which would increase the excitability of afferent endings innervating the colon.…”
Section: Concentrations Of Pro-inflammatory Cytokines Such As Interlementioning
confidence: 74%
“…Although the effects of CRF in the CNS are crucial to regulation of the GI tract, receptors are also expressed in the colon where they are ideally placed to mediate the effects of stress on gastric emptying, transit and gut motility. In support of the importance of peripheral regulation of GI function are studies demonstrating that stress-induced defecation and visceral hypersensitivity is attenuated by blocking peripheral CRF1 receptor activation (6,30,55). However, our studies also noted the potential role of inflammatory molecules in symptoms such as visceral pain and stress-induced defecation and the potential for crosstalk between stress and immune molecules in the manifestation of IBS symptom flares.…”
Section: The Neuromodulatory Effects Of Stress Peptides In Gut Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have shown that CRF may cause changes in the expression and distribution of TJ proteins [24, 25], resulting in the increased permeability of intestinal epithelial cells [26]. Moreover, CRF can induce changes in keratin expression [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…80,140 or in a variety of experimental models inducing visceral hyperalgesia including acute or repeated exposure to WAS alone or combined with neonatal maternal separation, consecutive sets of nociceptive CRD, repeated daily CRD 6 weeks after the development of colitis, intracolonic infusion of 0.5% acetic acid, or performing the CRD in a high-anxiety rat strain, the Wistar Kyoto (WKO). 80,90,[140][141][142][143][144][145][146][147][148][149][150][151][152] Likewise in CRF 1 receptor knockout mice, the visceral motor response to phasic CRD is reduced. 149 …”
Section: Corticotropin-releasing Factor Receptor 2 In the Colon: Modumentioning
confidence: 99%